اعتماد القرآن الكريم لتعليم اللغة العربية لغير ناطقيها (الجزء الثلاثون اختيارا) - محمد جواد حبيب البدراني (Prosiding Konferensi Nasional Bahasa Arab, 2020)
Arabic has a very important role in the field of culture and civilization, even in the field of religion, especially Islam. Arabic is the main language in the Qur’an and various Islamic worship rituals. So, to understand both, learning Arabic is very important to do, especially for foreign speakers. One strategy that can be applied to teach Arabic as a foreign language is to adopt the language of the Qur’an. The teachers can teach about Arabic grammar, speaking skills, reading skills, writing skills, and dictation, through short letters in the 30th chapter or Juz 'Amma. For example: 1) teaching grammar about the classification of kalam can be done through the analysis of surah al-Nasr and al-Masad, 2) teaching speaking skills can be done through questions and answers about surah al-Muthaffifin, 3) teaching reading skills can be done through the structural method then analytical method on the surahs in Juz 'Amma, and 4) teaching writing and dictating skills can be done through the surah al-Nasr by paying attention to the various forms of hamzah in it.Keywords: Arabic Language Teaching, The Qur’an, and Juz ‘Amma.